Strategic management practices in small and medium enterprises: A comprehensive systematic literature review - Mesfin Gezahegn; Kiruble Bruck (Universitas Nusa Cendana, 2026)
This research examines the extent to which small and medium-sized enterprises (SMEs) adopt strategic management practices throughout their organizational life cycle and identifies the key determinants influencing the selection of such practices. Given the critical role of SMEs in economic development and employment generation, understanding how these firms formulate and implement strategies is essential for enhancing their competitiveness and long-term sustainability. Employing a systematic literature review approach based on the PRISMA protocol, the study synthesizes evidence from research published between 2014 and 2024 in leading journals focusing on strategic management and small business management. The findings reveal that SMEs generally adopt less formalized and less structured strategic management processes than large corporations, primarily due to resource constraints, organizational flexibility, and managerial characteristics. However, SMEs compensate for this limitation through a greater reliance on visionary leadership, entrepreneurial orientation, and informal strategic decision-making processes that enable rapid adaptation to changing market conditions. The review further identifies a range of contextual and organizational factors that shape strategic management practices within SMEs, highlighting the unique nature of strategy formulation in smaller firms. By consolidating contemporary evidence on strategic management in SMEs, this study adds to the growing body of literature in strategic management and entrepreneurship.and provides a foundation for future research aimed at exploring the evolution, effectiveness, and contextual variations of strategic practices across different SME settings. Keywords: Small Business; Strategic Management; Strategic Planning